Hubungan Dukungan Ibu dengan Kesiapan Remaja Putri dalam Menghadapi Menarche - Sellia Juwita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the relationship between maternal support and the readiness of young women in dealing with menarche. The design in this study is quantitative analytic. Univariate results found that young women who received support from mothers were 49.2% and those who did not get support as much as 57.8%, adolescents who were prepared to face menarche were 57.4% and those who were not prepared were 42.6%. The results of bivariate analysis found that there is a relationship between maternal support and adolescent readiness in dealing with menarche where the p value is 0,000. Conclusion, adolescents who get maternal support are more prepared to face menarche compared to those who do not get support. Keywords: Mother Support, Readiness, Menarche, Youth